Comportamento estratégico e fatores críticos de sucesso: uma pesquisa em microcervejarias artesanais do Rio Grande do Sul - Drago, Henrique Faverzani (2019)
The survival and development of organizations in the competitive environment demands companies to continually seek for better strategies to carry out their processes, increase organizational performance and compete with products and services in a high quality standard, which demands a constant evolution, both in technology, as market demands. Therefore, if the company aims to achieve competitive advantage and organizational success, the response to change must be faster as possible, in front of situations faced inside and outside the organization. In this sense, this work had as objective examining the relationship between strategic behavior and critical success factors of the craft microbreweries in Rio Grande do Sul. For this purpose, the theoretical basis was based mainly on the teachings of Miles and Snow (1978), which refers to strategic behavior, and also in Rockart (1979), in relation to critical success factors. This analysis is important by the fact that even in the period of recession that Brazil had crossed, with innumerable companies finishing their activities, the branch of craft microbreweries presented a growth of more than 30% per year in the last four years. The type of research developed was quantitative, and the strategy used was a survey. The universe comprised all the craft microbreweries in the state of Rio Grande do Sul, which, as informed by the representative entities, consists around 253 companies, whether gypsy or not. The sample consisted of 120 companies from all regions of Rio Grande do Sul, where data collection was done by electronic means or in person. The results of the statistical analyzes identified that the analytical strategic behavior has a significant relation with the critical factors of success that have a high level of importance and that characterize both the organization and the manager, are: company reputation, entrepreneurial orientation, plans for management skills, hard work, human resources and innovation. Another significant relationship was between the strategic defender behavior and the critical success factors that presented an average level of importance to the organization, are: social responsibility and age of the company. It is worth noting that the analyzes are referring to the craft microbreweries of the state, and that this was a limiting factor, since it makes it impossible to generalize these results to the microbreweries throughout Brazil. As future studies, it is suggested to add to this research the construct "dynamic capacity" and "organizational performance", with the intention of expanding it at the national level, or who knows, to make a comparison with artisanal microbreweries from another country.